STUDENTS’ ACADEMIC PERFORMANCE, APTITUDE AND OCCUPATIONAL INTEREST IN THE NATIONAL CAREER ASSESSMENT EXAMINATION - Tan, Denis Abao; Balasico, Carmela Llagas (PUPIL: International Journal of Teaching, Education and Learning, 2018)
An investigation had been conducted to determine student’s academic performance, occupational interest and aptitude in the National Career Assessment Examination (NCAE) and ascertain predictors of their performance. This endeavor was put in place by the administration to have a research-based Senior High School curriculum that fits students need in Central Mindanao Laboratory High School. Results of NCAE from the Department of Education and grades of students from the laboratory high school records-in-charge were collected, coded, analyzed and interpreted. Data gathered within the three school year period became bases of the results of this research endeavor. Descriptive statistics showed that based on the NCAE results, students had better general scholastic aptitude but poor entrepreneurial skill. Occupational interests of students were so varied ranging from highly preferred to least preferred. Career in the sciences was moderately preferred by the students. Most of the students had no highly preferred occupation. Correlation showed that creativity was not associated with student’s academic performance while the rest such as, general scholastic aptitude (science ability, reading comprehension, verbal ability and mathematical ability), technical-vocational ability (clerical skill and visual manipulative skill), non-verbal ability, logical reasoning ability, and entrepreneurial skill (planning and decision making, budgeting, marketing and forecasting) were positively correlated to student’s performance. Stepwise linear regression analysis indicated that mathematical ability, verbal ability and logical reasoning ability were predictors of student’s academic performance